Inequalities in the health, nutrition, and wellbeing of Afrodescendant women and children: A cross-sectional analysis of ten Latin American and Caribbean countries - Janaína Calu Costa; Oscar J. Mujica; Giovanna Gatica-Domínguez; Sandra del Pino; Liliana Carvajal; Antonio Sanhueza; Sonja Caffe; Cesar G. Victora; Aluísio J.D. Barros (Elsevier, 2022)
Summary: Background: Afrodescendants are systematically affected by discrimination in the Americas and few multi-country studies addressed ethnic inequalities in health and wellbeing in the region. We aimed to investigate gaps in coverage of key health outcomes and socioeconomic inequalities between Afrodescendants and non-Afrodescendants populations in Latin American and Caribbean countries. Methods: Using national household surveys (2011-2019) from ten countries, we analyzed absolute inequalities between Afrodescendants and a comparison group that includes non-Afrodescendants and non-Indigenous individuals (henceforth non-Afrodescendants) across 17 indicators in the continuum of reproductive, maternal, newborn, child, and adolescent health. These include indicators of family planning, antenatal care, delivery assistance, child nutrition, immunization coverage, child protection, access to improved water, sanitation and hygiene, adolescent fertility, and early childhood mortality. Inequalities between country-specific subgroups of Afrodescendants were also explored. The slope index of inequality was used to assess wealth-based inequalities within each ethnic group. Findings: Afrodescendants represented from 2·8% (Honduras) to 59·1% (Brazil) of the national samples. Of the 128 combinations of country and indicators with data, Afrodescendants fared worse in 78 (of which 33 were significant) and performed better in 50 (15 significant). More systematic disadvantages for Afrodescendants were found for demand for family planning satisfied, early marriage, and household handwashing and sanitation facilities. In contrast, Afrodescendants tended to present lower c-section rates and lower stunting prevalence. Honduras was the only country where Afrodescendants performed better than non-Afrodescendants in several indicators. Wealth gaps among Afrodescendants were wider than those observed for non-Afrodescendants for most indicators and across all countries. Interpretation: Gaps in health outcomes between Afrodescendants and non-Afrodescendants were observed in most countries, with more frequent disadvantages for the former although, in many cases, the gaps were reversed. Wealth inequalities within Afrodescendants tended to be wider than for non-Afrodescendants. Funding: Pan American Health Organization, Bill and Melinda Gates Foundation, and the Wellcome Trust.